The Response of Indonesian Moslem University Students towards American Corner as the Product of Cultural Diplomacy (A Case Study on UPT American Corner UIN Walisongo Semarang) - CHANIFAH, MILLAH NUR (LANTERN (Journal on English Language, Culture and Literature), 2017)
in today’s civilization, cultural diplomacy as a soft approach in constructing beneficial relationship has remarkably been developed within the international circumstances. In case of American goverment, the United States also focuses on developing educational services in form of library center as the direct product of its cultural diplomacy which one of them is the construction of American Corner. Aligned with the American Corner UIN Walisongo Semarang, to measure response of its users towards American Corner as the product of cultural diplomacy is interesting, particularly from the students point of view whose educational backround has no relation with American Studies at all. This study applies a descriptive approach and quantitative method by distributing questionnaire towards 30 respondents. Theories used in this study are ‘American Cultural Diplomacy Product’ by Richard. T. Arndt and ‘Leader Characteristics and Foreign Policy Performance’ by Eugene R. Wittkopf. The data is presented in the form of tables and descriptive report. This study found that there is an ambiguity on the preference of Indonesian Moslem University Students towards the American cultural diplomacy product. Although they admit and realize with the political objectives of American Corner, they are still open to this political product since it brings beneficial features for their personal interests.